Objektivitas Pemberitaan Insiden Ejekan Asnawi Mangkualam Pada Situs Indosport.com - Jaya, Agung Kadarusman Mita; Suherdiana, Dadan; Chidayah, Prita Priantini Nur (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2020)
This study aims to determine the application of the principle of factuality and the principle of impartiality to the news regarding the incident of mockery of Asnawi Mangkualam published by indosport.com. This study uses a descriptive content analysis method with a qualitative approach which is implemented using the concept of objectivity from Jurgen Westershal where objectivity is divided into factuality and impartiality. while the data collection is done by means of documentation studies and literature studies of the news under study. Based on the results of this study, of the nine news articles studied, two news items did not meet the element of factuality, besides that there were two news stories that did not meet the element of impartiality